Targeted Partial Arthroscopic Trapeziectomy and Temporary K-Wire Distraction for Basal Joint Arthritis in Young Patients: A Retrospective Study of 39 Thumbs - de Villeneuve Bargemon, Jean-Baptiste; Rouveyrol, Mathias; Massin, Valentin; Jaloux, Charlotte; Levadoux, M. (Journal of Wrist Surgery, 2022)
Purpose There is a real need to find less invasive therapeutic options for young patients suffering from osteoarthritis of the first carpometacarpal joint. We wanted to assess the effectiveness of targeted partial arthroscopic trapeziectomy with distraction of the trapeziometacarpal (TM) joint with Kirschner wires (K-wires) in 39 thumbs impacted by TM osteoarthritis.Methods We conducted a retrospective study in which preoperative and postoperative data on pinch strength, grip strength, and pain on a visual analogue scale were collected. Subgroup analysis was performed based on two different K-wire distraction techniques. Only patients suffering from primary osteoarthritis and younger than 70 years were included. Second, we compared the frequency of complications relative to the position of the pins.Results We found a significant improvement in pain (p = 0.005) and grip strength (p = 0.0021) as well as an improvement in pinch strength (p = 0.5704). There was reduction in pain for all Badia levels, which was significant for stages 2 (p = 0.002) and 3 (p = 0.032) as well as an overall improvement in grip strength and pinch strength for all Badia levels.Conclusion Partial trapeziectomy with K-wire distraction in young patients suffering from TM osteoarthritis is a simple technique that requires minimal equipment and yields satisfactory outcomes. Conversion to another surgical treatment is still possible if this less invasive technique is unsuccessful.Level of Evidence This is a Level IV study.
Keywords: basal joint arthritis; thumb arthroscopy; hand; trapeziectomy